Perancangan dan Pembuatan Sistem Informasi Akuntansi Berbasis Web pada Toko Konveksi Gracia Sprei Tulungagung - Stefen Ongko Saputro; Silvia Rostianingsih (Jurnal Infra, 2020)
Until now Gracia sprei store still uses manual recording for every store administration activity like sales , purchases and the bookkeeping process. This make Gracia Store Owners think that their system still less efficient and looking for more effective recording methods.Looking at the source of the problems, a web based accounting information system was created to assist the recording process. This system was created using php language and MySQL database.The results obtained from this design process are record of the master data, record of transaction process, recording of production process, recording of the mutation , financial statements consisting of ledgers, balance sheets and journals